The potential for pesticide trunk injections for control of thousand cankers disease of walnut - DAL MASO, Elisa; LINALDEDDU, Benedetto Teodoro; FANCHIN, Genny; FACCOLI, Massimo; MONTECCHIO, Lucio (Phytopathologia Mediterranea, 2019)
Thousand cankers disease, caused by the pathogen Geosmithia morbida vectored by the bark beetle Pityophthorus juglandis, has emerged as an important disease of walnut trees in Europe. The present study was performed to evaluate the efficacy of trunk injections of four commercial fungicides and one insecticide for control of the fungus and its vector. Laboratory tests indicated that fungicides containing prochloraz + tetraconazole were the most effective. Field trials on non-infected trees allowed for the selection of a mixture containing prochloraz and tetraconazole (Binal Pro), the insecticide abamectin (Vertimec EC) and the adjuvant 2-(2-ethoxyethoxy) ethanol (CarbitolTM) as having rapid host uptake. Injections of this formulation in naturally infected black walnut trees reduced the presence of G. morbida, supporting trunk injection as an efficient and low impact technique to manage fungal damage on infected trees.